KONTRIBUSI PROGRAM EKSTRAKURIKULER SAINS DALAM MENINGKATKAN KOMPETENSI BELAJAR SISWA DI MADRASAH IBTIDAIYAH - Azka Faiqotul Himmah; Jamilatun Nafi'ah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science extracurricular programs in elementary schools are strategic activities that support the development of students’ learning competencies outside of formal instruction. This study aims to analyze the planning, implementation, supervision, and contribution of science extracurricular programs to the improvement of students’ learning competencies. The study employed a qualitative approach using a case study design at MIN 2 Jember, which was selected for its consistent achievement in science. Data were collected through in-depth interviews, participatory observation, and document analysis. The results indicate that the program was systematically designed based on the school’s vision, involved all stakeholders in its implementation, and was supported by progressive learning materials. Program implementation emphasized active student engagement through a “learning by doing” approach, such as experiments, observations, and competitions. Routine evaluations were conducted to ensure the program’s sustainability. This program contributes significantly to students’ conceptual understanding, critical thinking, problem-solving, and academic achievement. The novelty of this research lies in the development of a conceptual model for a structured science extracurricular program as an effective educational strategy to comprehensively enhance elementary school students’ learning competencies.